Nanoformulations of Herbal Extracts in Treatment of Neurodegenerative Disorders - Moradi, Seyed Zachariah; Momtaz, Saeideh; Bayrami, Zahra; Farzaei, Mohammad Hosein; Abdollahi, Mohammad (Frontiers in Bioengineering and Biotechnology, 2020)
Nanotechnology is one of the methods that have been able to influence human life in different ways and is a substantial tool that assists to overcome the multiple limitations in the treatment of various diseases, especially neurodegenerative disorders (NDs). Various nanostructures such as polymer nanoparticles, lipid nanoparticles, nanoliposomes, nano-micelle, carbon nanotubes (CNTs), besides different vehicle systems including poly lactic-co-glycolic acid, lactoferrin, polybutylcyanoacrylate and some others significantly increased the effectiveness, reduced the side effects, enhanced the stability, and improved the pharmacokinetics of several drugs. NDs belong to a group of annoying and debilitating disorders involving millions of people worldwide. Privious studies revealed that several nano formulations from a number of natural products such as curcumin (Cur), quercetin (QC), resveratrol (RSV), piperine (PIP), Ginkgo biloba, and Nigella sativa showed significant effectiveness in improving the condition of patients with NDs. The blood-brain barrier (BBB) is the main limitation of NDs management. In this review, we have attempted to discuss the effects of herbal-based nano formulation that used to treat such diseases. In summary, herbal-based nanoformulations seem to be significant in the treatment of NDs, alone or in combination with other drugs.